DOCTORS' KNOWLEDGE OF BREASTFEEDING ISSUES - Яков Яковлевич Яковлев; Владимир Иванович Фурцев; Марина Михайловна Котович; Елена Ивановна Лютина; Елена Германовна Сарычева; Марина Афанасьевна Соколовская; Ольга Александровна Загородникова (The Publishing House Medicine and Enlightenment, 2022)
Support for women during pregnancy and lactation has a positive effect on breastfeeding, as supported by many studies, including evidence-based medicine. Systematic reviews show the importance of professional support offered to health care providers in the postpartum period. However, a number of studies by Russian and foreign authors show insufficient training of doctors in breastfeeding support. The purpose of our study is to estimate basic knowledge of practitioners about support of breastfeeding, as the cheapest and easiest method of formation of the child's health. Materials and Methods. The multicenter study included 484 physicians of various specialties out of more than 500 questioned in 2019. Physicians were interviewed using electronic 308/484 (63.6 %) and paper 176/484 (36.4 %) versions of questionnaires. The total number of practicing physicians was 79.5 % of all respondents included in the study. The work experience in medicine was 18.0 (7.0; 30.0) years. The majority lived in the Ural (64.7 %) and Siberian (25.4 %) federal districts of the Russian Federation. The respondents were mostly women - 426/476 (89.5 %). The age of physicians was 43.0 (32.0; 54.0) years. Results. The data we obtained allow us to assess the level of doctors' knowledge of breastfeeding support. It is noteworthy that there is an insufficient understanding of the professional basic principles, which were established by WHO at the end of the XX century. There are still erroneous and outdated recommendations. A negative role in this is played by the denial of alternative sources of training on HB for pregnant and breastfeeding women by physicians. The low level of knowledge and rejection of WHO/UNICEF recommendations is a cause for concern. It is possible that this is a reflection of the lack of any positive change in breastfeeding rates in the Russian Federation over the past 12 years.